English for everyone. Course book. Level 2 beginner - Harding, Rachel (English teacher) (DK Publishing, 2024)
["Level 2 of] complete self-study English-language course that combines easy-to-use visual learning with crystal-clear grammar explanations, practice exercises, and free audio. This new edition includes a grammar reference section and full transcripts of the listening comprehension exercises."--from page 4 of cover.